1999
DOI: 10.1001/archneur.56.7.841
|View full text |Cite
|
Sign up to set email alerts
|

Validity of a Performance-Based Test of Function in Essential Tremor

Abstract: A valid performance-based test was developed to objectively assess functional capacity in patients with ET. This test would be useful in therapeutic trials, where it would provide an objective means to quantify the functional impact of tremor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
117
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 115 publications
(117 citation statements)
references
References 36 publications
0
117
0
Order By: Relevance
“…The total tremor score, ranging from 0 to 36, was the sum of these two (Louis et al 2002). The reliability of this videotape-based rating has been demonstrated by weighted kappa statistics of 0.62 -0.78, indicating substantial inter-rater agreement (Louis et al 1998) and the score correlates with other objective measures of tremor severity (Louis et al 1999). …”
Section: History and Examinationsmentioning
confidence: 85%
“…The total tremor score, ranging from 0 to 36, was the sum of these two (Louis et al 2002). The reliability of this videotape-based rating has been demonstrated by weighted kappa statistics of 0.62 -0.78, indicating substantial inter-rater agreement (Louis et al 1998) and the score correlates with other objective measures of tremor severity (Louis et al 1999). …”
Section: History and Examinationsmentioning
confidence: 85%
“…An in-person evaluation was performed on all participants, during which they completed demographic, medical history and family history questionnaires, and underwent a videotaped neurological examination, from which a total tremor score (range 0-36) was assigned. 10,[33][34][35][36][37] After review of the questionnaires and videotaped examinations, the diagnosis of ET was then reconfirmed by a senior neurologist specializing in movement disorders (EDL) using reliable and valid research criteria. 38 All ET diagnoses (possible, probable and definite) required, at a minimum, moderate or greater amplitude kinetic tremor on at least three tasks, and an absence of other etiologies (eg, dystonia, PD and drug-induced tremor).…”
Section: Study Participants and Clinical Diagnosismentioning
confidence: 99%
“…Tremor severity of the upper limbs was assessed according to the Fahn-Tolosa-Marin Tremor Rating Scale 20 and item "drinking from a cup" from the Washington Heights-Inwood Genetic Study of Essential Tremor Rating Scale. 21 The Tremor Rating Scale items included resting, postural, and action/intention tremor using the finger-tonose test (for each of these items, scores ranged from 0 5 no tremor to 4 5 severe tremor, with amplitude .4 cm); handwriting (0 5 normal; 4 5 severely abnormal, unable to keep pen on paper without holding the hand down); drawing (Archimedes spirals A large); and pouring water from one cup to another (0 5 normal, 4 5 unable to pour water without spilling most of it) and drinking from a cup (0 5 normal, 4 5 unable to hold the cup). The global tremor score was calculated as the sum of the above-mentioned items (total score 5 28 if writing was considered, 24 if not).…”
mentioning
confidence: 99%
“…We found that the tremor score improvement was correlated with the ADL improvement (r 5 0.68; p , 0.0001). To determine the functional outcome of GKT, we divided the cohort into 2 groups according to ADL improvement: improved patients (IPs) ($50%) and nonimproved patients (NIPs) (,50% [14][15][16][17][18][19][20][21][22] for NIPs and IPs, respectively). Neither the tremor etiology (PD or ET) nor the tremor score severity influenced the outcome.…”
mentioning
confidence: 99%